2015
DOI: 10.1177/1708538115589893
|View full text |Cite
|
Sign up to set email alerts
|

Competitive assessments of pulmonary embolism: Noninvasiveness versus the golden standard

Abstract: Diagnosis of suspected pulmonary embolism (PE) is crucial as undiagnosed and over-diagnosis can both lead to serious consequences. Contemporary diagnostic approach of PE is a sequential combination assessment beginning with clinical assessment, validated with D-dimer measurement and confirmed with pulmonary angiography or imaging. Since the invasive pulmonary angiography is risky and costly, imaging is a warranted tool in the diagnosis procedure. CT pulmonary angiography is a less-invasive method with general … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 83 publications
(94 reference statements)
0
3
0
Order By: Relevance
“…Acute pulmonary embolism (PE) has an annual incidence of approximately 3–6 cases per 10,000 persons in the general population [1, 2], and is the third leading cause of death responsible for an average of 650,000 deaths annually in the United States [35].…”
Section: Introductionmentioning
confidence: 99%
“…Acute pulmonary embolism (PE) has an annual incidence of approximately 3–6 cases per 10,000 persons in the general population [1, 2], and is the third leading cause of death responsible for an average of 650,000 deaths annually in the United States [35].…”
Section: Introductionmentioning
confidence: 99%
“… 15 , 16 Computed Tomography Pulmonary Angiography (CTPA) is reported as the “gold standard” for the diagnosis of APE. 17 However, patients with renal insufficiency and iodine-containing contrast agents hypersensitivity often limit its use. Moreover, the use of CTPA also has the problem of radiation exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Individual analysis of the signs indicated that right heart thrombus was not statistically significant for sensitivity or specificity while both the 60/60 sign and the tricuspid annular plane systolic excursion were only significant for specificity (Fields et al, 2017). While TEE can be useful to further evaluate a clinician's suspicion of PE, clinicians cannot exclude PE based on a normal TTE since not all PE will cause RV strain (Fields et al, 2017;Ma, Yan, Zhou, & Yuan, 2016;. Furthermore, in the situation of a PE, the TTE can help the clinician to quantify the hemodynamic consequences of a PE, to classify the severity of PE and guide therapy (Weekes et al, 2017).…”
Section: Transthoracic Echocardiogrammentioning
confidence: 99%